1990
DOI: 10.1111/j.1651-2227.1990.tb11414.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrofurantoin versus Trimethoprim Prophylaxis in Recurrent Urinary Tract Infection in Children

Abstract: ABSTRAm. Copenhagen study group of urinary tract infections in children (Departmentsmark.) Nitrofurantoin versus trimethoprim prophylaxis in recurrent urinary tract infection in children. A randomized, double-blind study. Acta Paediatr Scand 79: 1225,1990. The efficiency of nitrofurantoin and trimethoprim prophylaxis in preventing recurrent urinary tract infections (UTI) was compared by means of actuarial percentage recurrence-free c w e s in a randomized, double blind study in 130 children (126 girls, 4 boys)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(14 citation statements)
references
References 16 publications
0
12
0
2
Order By: Relevance
“…In the Brendstrup trial comparing nitrofurantoin to trimethoprim prophylaxis in children over 6 months, six of the 67 (9%) children randomized to nitrofurantoin carried strains resistant to it at baseline; during prophylaxis, 4/60 (7%) had at least one resistant bacterium. In contrast, although five of the 63 (8%) patients receiving trimethoprim carried bacteria resistant to this drug at baseline, 28/60 (47%) harboured a trimethoprim-resistant bacterium by the study's end [16]. No other studies provided both baseline and follow-up microbiological data.…”
Section: Emergence Of Resistancementioning
confidence: 99%
“…In the Brendstrup trial comparing nitrofurantoin to trimethoprim prophylaxis in children over 6 months, six of the 67 (9%) children randomized to nitrofurantoin carried strains resistant to it at baseline; during prophylaxis, 4/60 (7%) had at least one resistant bacterium. In contrast, although five of the 63 (8%) patients receiving trimethoprim carried bacteria resistant to this drug at baseline, 28/60 (47%) harboured a trimethoprim-resistant bacterium by the study's end [16]. No other studies provided both baseline and follow-up microbiological data.…”
Section: Emergence Of Resistancementioning
confidence: 99%
“…Five trials have compared one antibiotic with another [25][26][27][28][29], two of which compared cotrimoxazole with nitrofurantoin [26,29]. These two trials were small (N of 120 and 132) but both demonstrated statistically significant superiority of nitrofurantoin (risk ratios (RR) 0.57 (95 % CI 0.35-0.92) and 0.32 (95 % CI 0.19-0.56)).…”
Section: Antibiotic Treatmentmentioning
confidence: 99%
“…These two trials were small (N of 120 and 132) but both demonstrated statistically significant superiority of nitrofurantoin (risk ratios (RR) 0.57 (95 % CI 0.35-0.92) and 0.32 (95 % CI 0.19-0.56)). However, one study [26] reported 30 % of patients withdrawing from the study due to side effects of nitrofurantoin suggesting the acceptability of this treatment may be poor.…”
Section: Antibiotic Treatmentmentioning
confidence: 99%
“…The presence of E. coli resistant to trimethoprim has been demonstrated in up to 66% of children on antibiotic prophylaxis following breakthrough infection, suggesting that prophylaxis may play a role in inducing the emergence of antibiotic-resistant organisms (Braendstrup et al, 1990). Moreover, there is an 8-10% risk of adverse reactions with antimicrobial prophylaxis .…”
Section: Is There Any Harm Associated With the Long-term Use Of Antibmentioning
confidence: 99%